Transmandibular approach for upper cervical pathologies: Report of 2 cases and review of the literature - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2008)
In routine surgical practice, anterior approaches are not often used to treat Upper servical pathologies. Such lesions can be difficult to access surgically. This article describes 2 cases in which the transinandibular approach was used to address anterior upper cervical pathology. One case was a chordoma invading the C2-C3 vertebrae and the other case was atlanto-axial instability. Neurological examination revealed myelopathy in both cases. Each patient had already undergone occipito-cervical fusion at a different center and, thus, had limited neck extension and mouth-opening ability. In the first case, the tumor was totally excised. In the second, the dens was removed. We believe that the transmandibular approach is the best option for patients with limited neck mobility and restricted mouth-opening ability.
Keywords: atlanto-axial instability; cervical chordoma; transmandibular approach; TONGUE-SPLITTING APPROACH; SPINE; DECOMPRESSION